Large ethnic variations in recommended physical activity according to activity domains in amsterdam, the netherlands - Kunst Anton E; Agyemang Charles; van Valkengoed Irene GM; de Munter Jeroen SL; Stronks Karien (BMC, 2010)
Abstract Purpose The level of recommended physical activity (PA) is met less frequently by people from some ethnic minorities than others. We explored whether these differences in recommended PA between ethnic minority groups and the general population varied by domain and type of culturally-specific activity. Methods Participants were sampled from the population based SUNSET study and were from ethnic Dutch (n = 567), Hindustani-Surinamese (n = 370) and African-Surinamese (n = 689) descent. The validated SQUASH-questionnaire measured PA for the following domains: commuting, occupation, household, leisure time. Culturally-specific activities were added as extra question within the leisure time domain. The effect of each domain on ethnic differences in recommended PA prevalence was examined by odds-ratio (OR) analysis through recalculating recommended PA, while, in turn, excluding the contribution of each domain. Results In the ethnic Dutch population, more vigorous PA in commuting and leisure time was reported compared to the Surinamese groups. The Hindustani-Surinamese and African-Surinamese reported more walking as commuting activity, while the Dutch group reported cycling more frequently. Ethnic differences in recommended PA became smaller in both Surinamese groups compared with the Dutch after removing commuting activity, for example, in Hindustani-Surinamese men (OR = 0.92, 95%CI: 0.62-1.37 vs. OR = 1.33, 0.89-2.00) and women (OR = 1.61, 1.12-2.32 vs. OR = 2.03, 1.41-2.92). Removing occupational activity resulted in larger ethnic differences in both groups compared with the Dutch. Smaller effects were found for yoga and dancing, leisure time and household activities. Conclusion This study shows that differences in PA between ethnic minority groups and the general population vary according to the activity domain. The results indicate that including all relevant domains and activities is essential for assessment of ethnic differences in recommended PA.